Engaging voices: stakeholder consultations on IP&LC rights in the Colombian palm oil industry. A case study - Paipilla-Pardo, Leonardo; Dupre-Hardbord, Justin; Trip, Curtis; Varón, Margarita; Durán, Lisa; Estrada, María del Rosario; Rey, Andrea (Fedepalma, Cenipalma, 2025)
As part of its global sustainability agenda and human rights due diligence, Nestlé has committed to upholding the land rights of Indigenous Peoples (IPs) and Local Communities (LCs) within its supply chains, as outlined in its Human Rights Framework and Roadmap and Salient Issue Action Plan on Indigenous Peoples and Local Communities’ Land Rights (2023). Recognizing that land tenure security is a foundational element of environmental justice, responsible sourcing, and inclusive development, Nestlé expects all suppliers to ensure that land rights are respected throughout their operations.
Keywords: Derechos humanos; Agroindustria; Responsabilidad corporativa; Sector palmicultor